Evaluating Manual Mappings of Russian Proprietary Formats and Terminologies to FHIR - Lenivtceva, Iuliia D.; Kopanitsa, Georgy (Methods of Information in Medicine, 2019)
Background Evaluating potential data losses from mapping proprietary medical data formats to standards is essential for decision making. The article implements a method to evaluate the preliminary content overlap of proprietary medical formats, including national terminologies and Fast Healthcare Interoperability Resources (FHIR)—international medical standard.Methods Three types of mappings were evaluated in the article: proprietary format matched to FHIR, national terminologies matched to the FHIR mappings, and concepts from national terminologies matched to Systematized Nomenclature of Medicine–Clinical Terms (SNOMED CT). We matched attributes of the formats with FHIR definitions and calculated content overlap.Results The article reports the results of a manual mapping between a proprietary medical format and the FHIR standard. The following results were obtained: 81% of content overlap for the proprietary format to FHIR mapping, 88% of content overlap for the national terminologies to FHIR mapping, and 98.6% of concepts matching can be reached from national terminologies to SNOMED CT mapping. Twenty tables from the proprietary format and 20 dictionaries were matched with FHIR resources; nine dictionaries were matched with SNOMED CT concepts.Conclusion Mapping medical formats is a challenge. The obtained overlaps are promising in comparison with the investigated results. The study showed that standardization of data exchange between proprietary formats and FHIR is possible in Russia, and national terminologies can be used in FHIR-based information systems.
Keywords: proprietary format; FHIR; content overlap; medical records; mapping; SNOMED CT; terminology mapping